Practical analysis of the regimen for contesting the validity of corporate resolutions of a joint stock company - Véliz Ortíz, Samuel (2023)
In this paper, the author seeks to provide proposals to overcome the existing problems in the regime for challenging the validity of corporate resolutions of a corporation provided for in Law 26887, Ley General de Sociedades.For this purpose, the author first analyzes the nature of the corporate resolutions that may be adopted by a corporation. Subsequently, the author examines articles 38, 139 and 150 of the same law to provide answers to the problems that arise, mainly, with respect to the determination of the resolutions that can be contested under each article, the grounds that can be invoked, the active legitimacy to initiate the corresponding actions and the expiration periods that operate.